Politik Hukum Perlindungan dan Pengelolaan Lingkungan Hidup - Author: Sutrisno (Fakultas Hukum Universitas Islam Indonesia, 2011)
To utilize natural resources for the good of the people as mandated by the Constitution 1945 and to retrieve prosperity based on the Five Principles of Pancasila, a sustainable environmen preservation corresponding to the national growth is highly needed. Al-Quran is rich ofverses teaching mankind the necessity for them to preserve the nature as God has appointed mankind as the caliph of the earth. This research is a library research aimed at obtaining a vivid description on the implementation of Environmental Preservation and Management Constitution. Deductive and comparative method were implemented to analyze the data. The analysis pointed out that the authority for environmental management control lingered in deviation as it did not conform to the aims of the political law. Law enforcement faces barriers due to the difficulty to determine exact criteria and measurements of environmental damage. Therefore, dedication and professionalism from the law enforcers and the societal environmental awareness of the people were required to execute the laws governing the utilization of environment.